Leukositosis ekstrem pada seekor kucing domestik berusia 3 tahun dengan dislokasi panggul coxofemoral - Miftah Yanti; Nadissa Alika Rahma Herman; Sarasati Windria; Prananda Eka Rifki (ARSHI Veterinary Letters, 2025)
This paper reports the case of a 3-year-old domestic cat named Teyung, diagnosed with coxofemoral hip luxation through physical examination and X-ray imaging. Additional hematology diagnostics indicated extreme leukocytosis. The treatment administered included supportive therapy with Ringer's lactate infusion and injections of cefotaxime, gabapentin, and ondansetron. The patient did not show significant improvement over three days, and extreme leukocytosis was identified as the primary cause of death.